2022
DOI: 10.1177/00302228221086056
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Death Anxiety and COVID-19 Fear and Anxiety in Women With Breast Cancer

Abstract: This study determined the relationship between death anxiety and COVID-19 related fear and anxiety in women with breast cancer. This is a descriptive correlation-seeking study. The research included 140 women with breast cancer who visit the day treatment unit of the oncology department of a state university hospital. Personal Information Form, Fear of COVID-19 Scale (FCV-19S), Coronavirus Anxiety Scale (CAS), and Death Anxiety Scale (DAS) were used to collect data. A significant difference was found between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
1
2
0
1
Order By: Relevance
“…Consistent with previous studies (Afrashteh & Masoumi, 2021;Cella & Tross, 1987;Gonen et al, 2012;Kiyak & Polat, 2022;Krause et al, 2015;Loughan et al, 2020;Philipp et al, 2021;Sahan et al, 2018;Su et al, 2022;Zhou et al, 2020), higher levels of anxiety were associated with higher levels of cancer death anxiety. However, there was significant heterogeneity among the included studies.…”
Section: Psychosocialvariablessupporting
confidence: 91%
“…Consistent with previous studies (Afrashteh & Masoumi, 2021;Cella & Tross, 1987;Gonen et al, 2012;Kiyak & Polat, 2022;Krause et al, 2015;Loughan et al, 2020;Philipp et al, 2021;Sahan et al, 2018;Su et al, 2022;Zhou et al, 2020), higher levels of anxiety were associated with higher levels of cancer death anxiety. However, there was significant heterogeneity among the included studies.…”
Section: Psychosocialvariablessupporting
confidence: 91%
“…Turkish validation study of the scale developed by Lee (2020) reported a mean score of 6.66±2.65 (Evren et al, 2020). Another study reported a mean anxiety score of 1.35±2.60 in breast cancer patients in Türkiye (Kiyak and Türkben Polat, 2022). Moreover, in a study investigating the relationship between coronavirus anxiety and professional performance level in healthcare professionals working in emergency medical services, the mean anxiety score was reported as 1.95±1.10 (Hoşgör et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Benzer şekilde, Kıyak ve Türkben Polat'ın (2022) meme kanserli kadınlarda yaptıkları çalışmada, Covid-19 korkusunun ölüm anksiyetesini arttırdığı sonucuna ulaşılmıştır. 25 Yapılan diğer bir çalışmada, Covid-19 korkusu olanların aşı olma niyetlerinin daha yüksek olduğu ve kaygı ile birlikte anksiyetelerinin de yüksek olduğunu saptanmıştır. 26 Pandemi sürecinde ölüm sayılarına ilişkin veri paylaşımı, maske ve diğer koruyucu ekipmanların kullanımının medyada yayınlanması ve küresel ölüm hızlarının artması gibi durumlar bireyleri ve toplumu psikolojik olarak etkilemiştir.…”
Section: Discussionunclassified